Cardiovascular effects of Sp-CTx, a cytolysin from the scorpionfish (Scorpaena plumieri) venom. (August 2016) - Gomes, Helena L.; Menezes, Thiago N.; Malacarne, Pedro F.; Roman-Campos, Danilo; Gondim, Antonio N.; Cruz, Jader S.; Vassallo, Dalton V.; Figueiredo, Suely G.
Abstract: Fish venom cytolysins are multifunctional proteins that in addition to their cytolytic/hemolytic effects display neurotoxic, cardiotoxic and inflammatory activities, being described as "protein lethal factors". A pore-forming cytolysin called Sp-CTx ( S corpaenap lumieri C ytolyticT oxin) has been recently purified from the venom of the scorpionfish Scorpaena plumieri . It is a glycoprotein with dimeric constitution, comprising subunits of approximately 65 kDa. Previous studies have revealed that this toxin has a vasorelaxant activity that appears to involve the L-arginine–nitric oxide synthase pathway; however its cardiovascular effects have not been fully comprehended. The present study examined the cardiovascular effects of Sp-CTx in vivo and in vitro . In anesthetized rats Sp-CTx (70 μg/kg i.v) produced a biphasic response which consisted of an initial systolic and diastolic pressure increase followed by a sustained decrease of these parameters and the heart rate. In isolated rats hearts Sp-CTx (10 −9 to 5 × 10 −6 M) produced concentration-dependent and transient ventricular positive inotropic effect and vasoconstriction response on coronary bed. In papillary muscle, Sp-CTx (10 −7 M) also produced an increase in contractile isometric force, which was attenuated by the catecholamine releasing agent tyramine (100 μM) and the β-adrenergic antagonist propranolol (10 μM). On isolated ventricular cardiomyocytes Sp-CTx (1 nM) increased the L-type Ca 2+ current density. The results show that Sp-CTx induces disorders in the cardiovascular system through increase of sarcolemmal calcium influx, which in turn is partially caused by the release of endogenous noradrenaline. Highlights: In vivo Sp-CTx initially increased arterial pressure followed by a decrease. Sp-CTx induced ventricular positive inotropic effect and vasoconstriction. Sp-CTx increased Ltype Ca2+ current density on isolated cardiomyocytes. These disorders are partially caused by the release of endogenous noradrenaline.